Komparasi Kompetensi Profesional Guru Matematika SMP Berdasarkan Status Sertifikasi - Haryati Octaviani Bempah; Nurhayati Abbas; Ismail Djakaria (Department of Mathematics, Universitas Negeri Gorontalo, 2023)
This study aims to determine whether there are differences in the professional competency of certified and non-certified junior high school math teachers in Gorontalo City and District regarding teaching motivation. This research is an ex post facto study using a treatment by level 2 x 2 research design. The research was conducted in junior high schools throughout the City and District of Gorontalo in the odd semester of the 2022-2023 school year. Research data were obtained from teacher professional competency test instruments in multiple choice and teaching motivation questionnaires. Data analysis used Two Way Analysis of Variance to test the research hypothesis and further tests were carried out using the Scheffe test. The study results show that: (1) The professional competence of certified teachers is higher than uncertified teachers. (2) There is an interaction effect between certification status and teaching motivation on the professional competence of teachers. (3) In the group of teachers who have high motivation to teach, the professional competence of certified teachers is higher than teachers who are not certified. (4) In the group of teachers who have low motivation to teach, the professional competence of certified teachers is lower than teachers who are not certified. This condition is influenced by several factors such as self-awareness, training activities that are more oriented towards increasing pedagogical competence, and the absence of evaluation activities for post-certification teachers.